Access to treatment for drug users within the criminal justice system in European countries: systematic literature review, existing harm reduction initiatives in prisons, and models of good practice (ACCESS) - Stöver, Heino (Schriftenreihe "Gesundheitsförderung im Justizvollzug", 2014)
The EU-funded research project "ACCESS" provides an overview of the legislation, policy and practice concerning harm reduction services provided for problem drug users (PDUs) in European prisons in all of the European Union countries. This volume contains: A. A systematic literature review, B. An analysis of harm reduction measures in prisons, C. Best practice examples of harm reduction interventions in prisons. <engl.>